Point-of-care detection of sevoflurane anesthetics in exhaled breath using a miniature TOFMS for diagnosis of postoperative agitation symptoms in children. Issue 11 (10th May 2022) - Liu, Bing; Tang, Wenxi; Li, Hang; Liu, Ruidong; Dong, Fengshuo; Guo, Yingzhe; Li, Jianjun; Hou, Keyong
Abstract : A miniature TOFMS with MEPEI has been developed for POC diagnosis of postoperative agitation symptoms, and can analyze sevoflurane by direct sampling. The risk is high when the sevoflurane in the exhaled breath is higher than 500 ppmv. Abstract : In the operation using sevoflurane as an anesthetic, some patients, especially children, will have agitation symptoms after awakening from anesthesia. The incidence of agitation is about 20%, and current detection methods cannot predict the probability of a patient with agitation. In this paper, a magnetic field enhanced photoelectron ionization (MEPEI) miniature time-of-flight mass spectrometer (TOFMS) was developed for point-of-care detection and verification of the relationship between postoperative agitation symptoms and sevoflurane concentration in exhaled breath. The MEPEI source is water vapor resistant and can directly ionize sevoflurane via capillary sampling and obtain its characteristic ion [C4 H3 F6 O] + ( m / z 181), and the analysis time of exhaled breath is only 60 s. Three standard curves of 0.5–80 ppmv, 80–2000 ppmv and 2000–15 000 ppmv were formulated to quantitatively detect sevoflurane in different scenarios, the coefficient of determination ( R 2 ) was higher than 0.9882 and the relative standard deviation (RSD) of signal intensity was only 1.24%. The results indicated that four of the 46 child patients had agitation symptoms. Partial least squares-discriminant analysis (PLS-DA) was performed to analyze the data, and an identification and treatment strategy was established for child patients with agitation symptoms. The new miniature MEPEI-TOFMS was also successfully used to evaluate the concentration of sevoflurane in a medical environment. The real-time monitoring of sevoflurane concentration in exhalation indicates the potential of this method for low-cost and convenient point-of-care (POC) detection and diagnosis of agitation symptoms.